Controlled burning of peat before rewetting modifies soil chemistry and microbial dynamics to reduce short-term methane emissions - Shihao Cui; Haonan Guo; Lorenzo Pugliese; Claudia Kalla Nielsen; Shubiao Wu (Communications Earth & Environment)
Abstract Increased CH4 emissions from rewetted organic soils can undermine the climate benefits of reduced CO2 release. This is especially problematic in low-lying areas that tend to remain waterlogged and act as potential CH4 hotspots. Here we test whether burning the soil surface before rewetting can reduce CH4 emissions. Using laboratory experiments with soil cores collected from degraded farmland in Denmark, we found that rewetting organic soils following burning reduced CH4 emissions by more than 95% over a 90-day period compared to rewetting alone. The reduction was likely associated with changed soil chemistry such as increased soil carbon stability and the decrease in methanogen abundance and activity. Our results suggest that targeted burning could help suppress short-term CH4 emissions after rewetting. However, long-term field studies are needed to understand whether this effect persists and to assess potential ecological risks such as pollution runoff, before any broader field-scale implementation is considered.